2021
DOI: 10.13057/biodiv/d220534
|View full text |Cite
|
Sign up to set email alerts
|

Early growth evaluation and estimation of heritability in a sengon (Falcataria moluccana) progeny testing at Kediri, East Java, Indonesia

Abstract: Abstract. Nugroho A, Matra DD, Siregar IZ, Haneda NF, Istikorini Y, Rahmawati R, Amin Y, Siregar UJ. 2021. Early growth evaluation and estimation of heritability in a sengon (Falcataria moluccana) progeny testing at Kediri, East Java, Indonesia. Biodiversitas 22: 2728-2736. Sengon (Falcataria moluccana) is widely cultivated as a monoculture plantation in community forests that still poses a high risk of pest and disease attacks.  Although plants naturally show signs of resistance, there is still however a lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The endophytic fungi used in this study were isolated from the seeds of sengon, namely Ochroconis sp., Cladophialophora sp., Ascotricha sp., and Aspergillus sp. (Istikorini et al 2021). Isolates of endophytic fungi were rejuvenated and propagated on Potato Dextrose Agar (PDA) medium and then incubated for 14 days at room temperature.…”
Section: Rejuvenation and Propagation Of Endophytic Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…The endophytic fungi used in this study were isolated from the seeds of sengon, namely Ochroconis sp., Cladophialophora sp., Ascotricha sp., and Aspergillus sp. (Istikorini et al 2021). Isolates of endophytic fungi were rejuvenated and propagated on Potato Dextrose Agar (PDA) medium and then incubated for 14 days at room temperature.…”
Section: Rejuvenation and Propagation Of Endophytic Fungimentioning
confidence: 99%
“…The production of sengon wood has increased from 3,651,479 m 3 in 2018 (BPS 2018) to 5,468,716 m 3 in 2019 (BPS 2019). Sengon is a fast-growing species capable of substituting wood materials widely used in reforestation and restoration programs (Nugroho et al 2021). In addition, sengon leaves can be used as animal feed because they contain high protein (Hartanto 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research institutions, universities and companies carry out research on tree species, mostly native ones, covering areas such as population genetics, breeding and silvicultural practices (e.g., [81][82][83][84][85]). In some cases, information from the trials is used for provenance selection in planting programs [86].…”
Section: Selection and Innovationmentioning
confidence: 99%
“…Indonesia Health Data Profile 2010 revealed that pulp and periapical diseases are found in the 7 th of the ten most common diseases of outpatients in Indonesian Hospitals [3][4][5][6]. According to the Health Profile of Surakarta in 2014, the prevalence of pulp abnormalities and periapical tissue was 16,186 cases (2,56%) from the data of outpatient disease patterns in Surakarta Community Health Centre [4][5][6][7][8][9]. However, the distribution data of pulp disease remain obscure.…”
Section: Introductionmentioning
confidence: 99%